2007
DOI: 10.1111/j.1399-3089.2007.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Babesia as a complication of immunosuppression following pig‐to‐baboon heart transplantation

Abstract: We report a baboon that developed anemia, leukocytosis, fever, and anorexia while immunosuppressed following a pig heart transplant. Blood smears indicated babesia infection of the erythrocytes, and this was confirmed by polymerase chain reaction. A 1-week course of treatment with doxycycline successfully eradicated the organism. Babesia, a widespread blood parasite that can infect humans, has been reported to be present in the erythrocytes of approximately a third of baboons housed in facilities in the USA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…It has been reported that side effects related to immunosuppressive therapy in xenotransplanted primates may lead to severe complications for recipients even in the absence of xenograft rejection . In particular, we and others have previously reported that, both in transplanted and control animals, immunosuppressants may cause severe GI tract complications in cynomolgus monkeys and baboons, leading to premature euthanasia .…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that side effects related to immunosuppressive therapy in xenotransplanted primates may lead to severe complications for recipients even in the absence of xenograft rejection . In particular, we and others have previously reported that, both in transplanted and control animals, immunosuppressants may cause severe GI tract complications in cynomolgus monkeys and baboons, leading to premature euthanasia .…”
Section: Discussionmentioning
confidence: 88%
“…Ezzelarab et al. reported the case of a baboon that developed anemia, leukocytosis, fever and anorexia following pig heart xenotransplantation [18]. They identified Babesia as the cause of this clinical syndrome.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Unfortunately due to the genetic disparity and to the requirement for significant immuno-suppression, many complications have been recorded,13 including disseminated intravascular coagulopathy (DIC) and other coagulopathies 47. In addition to drug side effects, several other complications occur in this model due to need for central intravenous lines; requiring restraining jackets and tethers.…”
mentioning
confidence: 99%